Growth patterns of freshwater (Anadonta woodiana) water-based on the substrate in Aron Patah river waters of Panga district, Aceh Jaya district - Nurul Fajrina; M. Ali Sarong; Mimie Saputri; Ismul Huda; Khairil Khairil (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Growth is the process of increasing the volume and number of cells so that the size of the body of living things increases. Anodonta woodiana is a species of freshwater mussel as macrozoobenthos that lives in fresh waters and has a relatively sedentary nature. This study aims to determine (1) growth patterns and (2) Anadonta woodiana habitat characteristics based on substrates in the waters of the Aron Patah River, Panga District, Aceh Jaya Regency. This research was conducted in June to July 2019. The type of research used in this research is quantitative descriptive. The method used in this study is a survey method with purposive sampling technique. The location of this study was divided into 3 observation stations. Data were analyzed with the formula of growth patterns and environmental conditions analyzed descriptively. The results showed that the constant value of the estimation of growth pattern (b) ranged from 1.9602 to 2.3681. Habitat characteristics at station I have sand substrate while at station II and III have substrate sand, temperature ranges from 27ºC - 30ºC, with pH ranging from 7.2 - 7.8 and salinity ranges from 24‰ - 30‰. Macrobenthos found in this study were Melanoides torulosa, Paphila undulata, and Pila ampullacea. Vegetation found Hibiscus tiliaceus, Imperata cylindrica, Casuarina equisetifolia and Eichornia crassipes. Based on the results of the study it can be concluded that the growth pattern of A.woodiana in the Aron Patah River waters is negative allometric.Keywords: Growth patterns, Anadonta woodiana, Habitat, RiverPertumbuhan adalah proses pertambahan volume dan jumlah sel sehingga ukuran tubuh makhluk hidup bertambah besar. Anodonta woodiana adalah salah satu spesies kerang air tawar sebagai makrozoobenthos yang hidup di perairan tawar dan mempunyai sifat hidup yang relatif menetap. Penelitian ini bertujuan untuk mengetahui (1) Pola pertumbuhayangn dan (2) Karakteristik habitat A. woodiana berdasarkan substrat di perairan Sungai Aron Patah Kecamatan Panga Kabupaten Aceh Jaya. Penelitian ini dilakukan pada bulan Juni sampai Juli 2019. Jenis penelitian yang digunakan pada penelitian ini adalah deskriptif kuantitatif. Metode yang digunakan dalam penelitian ini adalah metode survey dengan teknik Purposive sampling. Lokasi penelitian ini dibagi kedalam 3 stasiun pengamatan. Data dianalisis dengan rumus pola pertumbuhan dan kondisi lingkungan dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa nilai konstanta penduga pola pertumbuhan (b) berkisar 1,9602-2,3681. Karakteristik habitat pada stasiun I bersubstrat pasir sedangkan pada stasiun II dan III bersubstrat lempung psasir, suhu berkisar antara 27ºC - 30ºC, dengan pH berkisar antara 7,2 - 7,8 dan salinitas berkisar antara 24‰ – 30‰. Makrobenthos yang temukan pada penelitian ini Melanoides torulosa, Paphila undulata, dan Pila ampullacea. Vegetasi yang temukan Hibiscus tiliaceus, Imperata cylindrica, Casuarina equisetifolia dan Eichornia crassipes. Berdasarkan dari hasil penelitian dapat disimpulkan bahwa pola pertumbuhan A.woodiana di perairan Sungai Aron Patah bersifat allometrik negatif.Kata kunci: pola pertumbuhan, Anadonta woodiana, habitat, sungai